Commercial indium recovery processes development from various e-(industry) waste through the insightful integration of valorization processes: A perspective. (15th March 2019) - Swain, Basudev; Lee, Chan Gi
Highlights: Waste-to-waste stream mixed process for indium recovery is proposed. Mixed stream process can address gap between leaching and purification processes. Brings back the material to production stream and address the circular economy. Abstract: Recycling of the waste LCD and recovery of indium which is an important classified critical raw material rarely have been industrially valorized for the circular economy due to lack of technology. Waste specific technology development is a cost-intensive and time-consuming process for the recycling industry. Hence, integrating existing technology for the purpose can address the e-waste issue in general and waste LCD in particular. Waste LCD and LCD industry itching wastewater are two important challenges can be addressed through an insightful combination of two. Hence, here possible integration of waste LCD leaching process with ITO wastewater treatment has been focused on indium recovery purpose. From our perspective process integration can be managed in two different ways, i.e., waste-to-waste mix stream process and integration of two different valorization processes for complete recovery of indium. With reference to indium recovery and context of e-waste recovery the process integration can be managed in two different ways, i.e., (i) waste LCD leaching with ITO etching industry wastewater then valorized (Waste-to-waste mix stream), (ii) Integration of waste LCD leaching process with ITO wastewater treatment process (integration of two valorization processes).Through proposed process semiconductor manufacturing industry and ITO recycling industry can address various issues like; (i) waste disposal, as well as indium recovery, (ii) brings back the material to production stream and address the circular economy, (ii) can be closed-loop process with industry and (iii) can be part of cradle-to-cradle technology management and lower the futuristic carbon economy, simultaneously.